Eficácia da betametasona intralesional versus triancinolona acetonida no tratamento da alopecia areata - Sousa, Vando Barbosa de (2020)
Alopecia areata is a relatively common disease that affects hair follicles, with a cumulative lifetime incidence of around 2%. Typically, it is manifested with the sudden appearance of well defined, circular areas of alopecia, without inflammatory signs on the scalp. Its pathogenesis is not yet fully understood, but strong evidence makes us believe it is an autoimmune disorder. Numerous forms of treatment have been studied. In its most typical, plaque and localized presentation, the use of intralesional corticosteroids is the first-line of therapy. The literature is unanimous in indicating intralesional triamcinolone acetonide as the therapy of choice. Although this treatment modality has been used for over 60 years, the use of other corticosteroids such as betamethasone is poorly studied. In some countries, such as Brazil, triamcinolone acetonide is not commercially available , its less soluble derivative triamcinolone hexacetonide or betamethasone is then used. For having an excessively long half -life, triamcinolone hexacetonide is less suitable for intralesional use . Although intralesional betamethasone is often used in Brazil, to date, there is insufficient evidence in the literature to indicate the best concentration for use in AA, nor its efficacy . This study aims to evaluate the effectiveness and safety of using intralesional betamethasone when compared to triamcinolone acetonide. A within-patient double blind (patient and examiner) randomized controlled trial was performed. We recruited 12 patients with alopecia plaque divided into four quadrants. Each quadrant, after randomization, received an intralesional injection with one of the following treatments: triamcinolone acetonide 2.5 mg/ml, betamethasone 0.375mg/ml, betamethasone 1.75mg/ml, or 0.9% saline (placebo). The intervention was repeated in the same quadrant every 4 weeks, totaling 3 sessions. Visual and dermoscopic evaluation of the results were performed. At 4 and 8 weeks of intervention, triamcinolone acetonide 2.5 mg/ml provided the best visual results. Nevertheless, at the end of the study, the best visual results were seen with both triamcinolone acetonide and betamethasone 1.75mg/ml, with significant difference when compared to betamethasone 0.375mg/ml and placebo (p=.0489 and <.0001, respectively). There was a progressive reduction in the number of dystrophic hairs in all intervention quadrants and placebo; however, the reduction was faster in the intervention quadrants. No local adverse effects were observed in any of the patients. Triamcinolone acetonide shows earlier results in repilation, but at 8 and 12 weeks betamethasone at a concentration of 1.75mg/ml had similar results to triamcinolone acetonide. Thus, intralesional betamethasone seems to be a safe and effective therapeutic option in alopecia areata.